Dysautonomia in Autism Spectrum Disorder: Case Reports of a Family with Review of the Literature. (31st May 2011) - Lonsdale, Derrick; Shamberger, Raymond J.; Obrenovich, Mark E.
Abstract : Case histories of a mother and her two children are reported. The mother was a recovered alcoholic. She and her two children, both of whom had symptoms that are typical of autistic spectrum disorder, had dysautonomia. All had intermittently abnormal erythrocyte transketolase studies indicating abnormal thiamine pyrophosphate homeostasis. Both children had unusual concentrations of urinary arsenic. All had symptomatic improvement with diet restriction and supplementary vitamin therapy but quickly relapsed after ingestion of sugar, milk, or wheat. The stress of a heavy metal burden, superimposed on existing genetic or epigenetic risk factors, may be important in the etiology of autism spectrum disorder when in combination. Dysautonomia has been associated with several diseases, including autism, without a common etiology. It is hypothesized that oxidative stress results in loss of cellular energy and causes retardation of hard wiring of the brain in infancy, affecting limbic system control of the autonomic nervous system.